Newer indications for neuromonitoring in critically ill neonates - Variane, Gabriel F. T.; Pietrobom, Rafaela F. R.; Noh, Caroline Y.; Van Meurs, Krisa P.; Chock, Valerie Y. (Frontiers in Pediatrics, 2023)
Continuous neuromonitoring in the neonatal intensive care unit allows for bedside assessment of brain oxygenation and perfusion as well as cerebral function and seizure identification. Near-infrared spectroscopy (NIRS) reflects the balance between oxygen delivery and consumption, and use of multisite monitoring of regional oxygenation provides organ-specific assessment of perfusion. With understanding of the underlying principles of NIRS as well as the physiologic factors which impact oxygenation and perfusion of the brain, kidneys and bowel, changes in neonatal physiology can be more easily recognized by bedside providers, allowing for appropriate, targeted interventions. Amplitude-integrated electroencephalography (aEEG) allows continuous bedside evaluation of cerebral background activity patterns indicative of the level of cerebral function as well as identification of seizure activity. Normal background patterns are reassuring while abnormal background patterns indicate abnormal brain function. Combining brain monitoring information together with continuous vital sign monitoring (blood pressure, pulse oximetry, heart rate and temperature) at the bedside may be described as multi-modality monitoring and facilitates understanding of physiology. We describe 10 cases in critically ill neonates that demonstrate how comprehensive multimodal monitoring provided greater recognition of the hemodynamic status and its impact on cerebral oxygenation and cerebral function thereby informing treatment decisions. We anticipate that there are numerous other uses of NIRS as well as NIRS in conjunction with aEEG which are yet to be reported.